2021
DOI: 10.1109/access.2021.3057237
|View full text |Cite
|
Sign up to set email alerts
|

“Pencil Beamforming Increases Human Exposure to ElectroMagnetic Fields”: True or False?

Abstract: According to a very popular belief -very widespread among non-scientific communitiesthe exploitation of narrow beams, a.k.a. ''pencil beamforming'', results in a prompt increase of exposure levels radiated by 5G Base Stations (BSs). To face such concern with a scientific approach, in this work we propose a novel localization-enhanced pencil beamforming technique, in which the traffic beams are tuned in accordance with the uncertainty localization levels of User Equipment (UE). Compared to currently deployed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…There have been many research efforts on assessing the EMF exposure based on measurements [9]- [15] and simulations [16]- [18] in the past years. In general, the EMF exposure originates from two possible sources, i.e., (i) uplink signal from user equipment (UE), and (ii) downlink signal from BSs [19].…”
Section: A Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been many research efforts on assessing the EMF exposure based on measurements [9]- [15] and simulations [16]- [18] in the past years. In general, the EMF exposure originates from two possible sources, i.e., (i) uplink signal from user equipment (UE), and (ii) downlink signal from BSs [19].…”
Section: A Related Workmentioning
confidence: 99%
“…A comparison of human exposure in terms of SAR and PD under different wireless technologies was performed in [17]. Recently, the effect of massive MIMO on the EMF exposure has been further studied in [18], where the authors revealed that the pencil beamforming could be beneficial for network throughput and reduce the EMF level. However, the simulation studies in [16]- [18] considered the standard regular hexagonal model for BS locations, which is not sufficiently accurate for the current BS deployment that requires irregular network topologies due to the variation demand of network capacity and various communication environments, e.g., residential areas, high-rise building, and rural areas.…”
Section: A Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…We have performed a preliminary analysis for the impact of pencil beamforming on the QoS of 5G networks and the ElectroMagnetic field (EMF) exposure. To this aim, an open-source simulator has been developed [9] that is able to synthesize the traffic beams for each gNB, both in direction and beamwidth, by exploiting user equipment (UE) localization accuracy. Each beam is directed towards the centre of a circular area in which the UE is assumed to be, where the diameter Table I presents the values of the average EMF [V/m] and the average throughput [Mbps] according to different location uncertainty levels.…”
Section: B Network-centric Location-based Analyticsmentioning
confidence: 99%
“…On the one hand, most of the works are carried out in outdoor scenarios and present EMF assessments focused on the downlink (DL) of a 5G system. The work presented in Reference [6] proposed a simulation technique to assess EMF exposure in 5G cellular systems operating at sub-6 GHz frequencies. The novelty of their work is that they propose a localization-enhanced pencil beamforming technique in which the traffic beams are tuned in accordance with the uncertainty localization levels of the User Equipment (UE) in the DL configuration.…”
Section: Introductionmentioning
confidence: 99%